Transient acute flaccid paralysis and seizures associated with rotavirus gastroenteritis in a child - Özalp, Ezgi; Aydın-Teke, Türkan; Tanır, Gönül; Özkan, Mehpare; Bayhan, Gülsüm İclal (The Turkish Journal of Pediatrics, 2012)
Rotavirus is a common cause of acute gastroenteritis in young children. Neurological complications including seizures are known to accompany rotavirus gastroenteritis. Acute flaccid paralysis (AFP) associated with rotavirus has not been reported previously except for one report. Herein, we describe a case of transient AFP and seizures associated with rotavirus gastroenteritis. We think that transient AFP can be seen during mild rotavirus gastroenteritis in children, but further studies may be necessary to understand the role of rotavirus as a cause of AFP in children.